Social Media Facebook in Rural Communities (Case Study of Bandar Klippa Village Community against Changes in Communication Psychology) - Akbar Aldi Kautsar; Mailin; Ade Soraya; Mas Khairani (Budapest International Research and Critics University, 2022)
This research is entitled